2020
DOI: 10.3390/toxins12010032
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Neurotoxins and Cancer—A Review of the Literature

Abstract: Botulinum neurotoxins (BoNT) possess an analgesic effect through several mechanisms including an inhibition of acetylcholine release from the neuromuscular junction as well as an inhibition of specific pain transmitters and mediators. Animal studies have shown that a peripheral injection of BoNTs impairs the release of major pain transmitters such as substance P, calcitonin gene related peptide (CGRP) and glutamate from peripheral nerve endings as well as peripheral and central neurons (dorsal root ganglia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 81 publications
0
28
0
2
Order By: Relevance
“…BoNT also downregulates sensory receptors, such as transient receptor potential cation channel subfamily V member 1 (TRPV1), also known as the capsaicin receptor and the vanilloid receptor 1, and purinergic (P2X3) receptors [ 280 ]. BoNT’s effects on these transmitters and receptors is being explored in the management of autonomic and pain disorders such as those associated with cancer [ 281 ].…”
Section: Discussion Of Bont Use In Different Indicationsmentioning
confidence: 99%
“…BoNT also downregulates sensory receptors, such as transient receptor potential cation channel subfamily V member 1 (TRPV1), also known as the capsaicin receptor and the vanilloid receptor 1, and purinergic (P2X3) receptors [ 280 ]. BoNT’s effects on these transmitters and receptors is being explored in the management of autonomic and pain disorders such as those associated with cancer [ 281 ].…”
Section: Discussion Of Bont Use In Different Indicationsmentioning
confidence: 99%
“…The anticoagulants tyrofabin and hirudin, for example, originate from venom of the African saw-scaled viper and leech secretions, respectively [1]. Even pathogenic bacteria typically considered harmful to healthy tissue may prove to be clinically useful as studies have shown that toxins produced by these organisms can be manipulated to target aberrant cells in a tissue-or cell-specific manner [2][3][4][5].…”
mentioning
confidence: 99%
“…In this Special Issue, we explore how toxins may be used as powerful treatments against certain cancers. The compiled articles cover how naturally-derived poisons can be utilized for cancer therapy on multiple levels, from interrogating cytotoxic pathways in different cell types, to exploiting toxic derivatives for pain relief in patients suffering from radiation sickness [3,5]. The Special Issue presented this month helps to expound upon this field of research and demonstrate the potential for its clinical applicability.…”
mentioning
confidence: 99%
See 2 more Smart Citations